(untitled) (Fiep Bulletin - online, 2012)
In this article we will try to inform of the deep legislative evolution regarding the new professional degrees for technicians in sport careers during the last decade in Spain. During this decade, big legislative transformations have been made as a result of the interest shown by the institutions for solving the multiple and important deficiencies of the professional degrees granted by the Sport Federations. Thus, we pretend this legislative evolution can be useful for being expanded to other countries, so the professionals of Sport Management know the situation in Spain.